PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN PEMILIK DAN PEMAHAMAN AKUNTANSI TERHADAP PERSPSI PEMILIK HOMESTAY DI DESA WISATA PINGE ATAS LAPORAN KEUANGAN - I Gede Dirga Surya Arya Widhyadanta (Jurnal Widya Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the impact of homestay owners' perceptions of Pinge Tourism Village financial reporting by their level of education, accounting experience, and understanding. The data collection method in this study was based on a questionnaire distributed to the respondents. The sample for this survey was a homestay owner from Pinge Tourist Village, and 51 of them were the respondents. The analytical technique used is multiple linear regression. Test results show that an owner's education level, accounting understanding, and experience have a positive impact on host family owners' perceptions of financial